Ta’wil Al-Qur’an Imam Al-Ghazali: Telaah Metodologis atas Kitab Tafsir al-Imam al-Ghazali Karya Muhammad al-Rihani - Basid, Abd.; Naufal Maulana, Ach.; Robith Lutfillah, Wahid (Prodi IAT STAI Al Akbar Surabaya, 2023)
The figure of the author of the book Ihya' 'Ulum al-Din, Imam Al-Ghazali, in the field of interpretation is not yet widely known by the public, even though he has made quite a large contribution to the discourse on the study of interpretation of the Qur'an, with his intelligent and